LINGUOSEMIOTIC CLASSIFICATION OF SYMBOLS - pcadmin, Usmanova Khumora Akhmadjonovna (Scholar Express Journals, 2025)
Linvosemiotic classification of symbols in Uzbek poetry is analyzed in the article, their lexical meaning and semantic features are highlighted.
Keywords: Uzbek poetry; symbols; linguosemiotics